2021
DOI: 10.1063/5.0031712
|View full text |Cite
|
Sign up to set email alerts
|

Periodic fluctuations of streamwise vortices in inertia-dominated intersecting flows

Abstract: In the proximity of stagnation points, flow instabilities tend to arise at relatively low Reynolds numbers (Re). These instabilities often manifest as vortices that can evolve time-periodic patterns as Re is increased. These types of flows are well studied in cases for which the stagnation point is fixed on an obstacle and the resulting vortices are in the spanwise direction (e.g., the von Kármán vortex street). However, they are less understood in intersecting flows, where the stagnation point is not wall-att… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 82 publications
0
14
0
Order By: Relevance
“…Previous studies have demonstrated that the simulation method used in current study is suitable for steady and unsteady inertial vortical flows in micro mixers, especially for steady engulfment flows. ,,, In current work, on the basis of previous work, ,, the applicability of the adopted simulation method for the unsteady flows is further validated. As shown in Figure S2, experimental and simulated dye concentrations on plane z / h = 0 for w i / h = 0.3 and Re = 400 at five moments in a period are compared.…”
Section: Numerical Methodologymentioning
confidence: 88%
See 2 more Smart Citations
“…Previous studies have demonstrated that the simulation method used in current study is suitable for steady and unsteady inertial vortical flows in micro mixers, especially for steady engulfment flows. ,,, In current work, on the basis of previous work, ,, the applicability of the adopted simulation method for the unsteady flows is further validated. As shown in Figure S2, experimental and simulated dye concentrations on plane z / h = 0 for w i / h = 0.3 and Re = 400 at five moments in a period are compared.…”
Section: Numerical Methodologymentioning
confidence: 88%
“…It should be pointed out that flow regimes are also sensitive to geometrical parameters of cross-shaped mixers. , By 2D and 3D numerical simulations, Correa et al , analyzed the influence of w i / h and crossing angles (the angle between the inlet channel and the mixing chamber) on the development of vortices in cross-shaped mixers. It was found that, as w i / h increases from 1 to 11, the number of vortices increases from 1 to 4.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Second, streamwise vortices are known to develop in water downstream of the cross junction at moderately high Reynolds numbers (onset Re = 107 for a channel height to width ratio of 0.45) comparable to those used in the current study. 38 The presence of such asymmetric vortices could lead to asymmetric splitting of cells. When cell splitting was performed at a Reynolds number of 346 ( v e = 2.08 m/s), we noticed that in some cases, there was flapping of the “tail” region of the fragment immediately following the split (Movie S1).…”
Section: Resultsmentioning
confidence: 99%
“…Second, streamwise vortices are known to develop in water downstream of the cross junction at moderately high Reynolds numbers (onset Re = 107 for a channel height to width ratio of 0.45) comparable to those used in the current study. 49 The presence of such asymmetric vortices could lead to asymmetric splitting of cells. When cell splitting was performed at a Reynolds number of 346 (v e = 2.08 m s −1 ), we noticed that in some cases, there was flapping of the "tail" region of the fragment immediately following the split (Movie S1 †).…”
Section: Characterization Of Splitting Probability and Symmetrymentioning
confidence: 99%